RNA sequencing of drug combinations for SL-176 and GSK-J4 in neuroblastoma cell lines - Treis, Diana; Wickström Näsman, Malin (Karolinska Institutet, 2025)
High-risk neuroblastoma remains a deadly disease with a survival rate of only 50-60 %. Prognosis is particularly poor in children who relapse after chemotherapy. In light of this, increasing attention has been directed toward the development of targeted therapies for neuroblastoma.

Drug combination screening and follow-up experiments have shown that the WIP1 inhibitor SL-176 and the H3K27 demethylase inhibitor GSK-J4 act synergistically against neuroblastoma cells. To understand the mechanisms behind this synergism, we have treated cells of neuroblastoma cell lines IMR-32 and SK-N-BE(2) with either vehicle, SL-176, GSK-J4, or the combination of both drugs for 72 hours and performed RNA sequencing (Illumina NextSeq 550).

Total RNA was subjected to quality control with the Agilent TapeStation (Agilent Technologies, Santa Clara, CA, USA) according to the manufacturer’s instructions. To construct libraries suitable for Illumina sequencing, the Illumina TruSeq Stranded mRNA sample preparation protocol which includes mRNA isolation, cDNA synthesis, ligation of adapters and amplification of indexed libraries was used. The yield and quality of the amplified libraries was analyzed using Qubit by ThermoFisher and the Agilent TapeStation. The indexed cDNA libraries were normalized and combined, and the pools were sequenced on the Illumina NextSeq 550 (Illumina, San Diego, CA, USA) for a 75-cycle v2 sequencing run generating 75 bp single-end reads. Basecalling and demultiplexing was performed using CASAVA software (Illumina) with default settings generating Fastq files for further downstream mapping and analysis. Raw data was adapter and quality trimmed using Cutadapt, and aligned to the human genome build (Gene reference: Ensembl Homo_sapiens.GRCh38.104.gtf) using STAR. Gene assignment was performed using FeatureCounts. Differential gene expression was determined using DEseq2.

Läkemedelskombinationsscreening och uppföljande experiment har visat att WIP1-hämmaren SL-176 och H3K27-demethylashämmaren GSK-J4 verkar synergistiskt i neuroblastomceller. För att förstå mekanismerna bakom denna synergism har vi behandlat celler från neuroblastom-cellinjerna IMR-32 och SK-N-BE(2) med antingen vehikel, SL-176, GSK-J4 eller en kombination av båda läkemedlen i 72 timmar och genomfört RNA-sekvensering (Illumina NextSeq 550).

För ytterligare beskrivning av RNA-sekvensering och dataanalys, se beskrivning på engelska.
RNA-sekvensering av kombinationsbehandling med SL-176 och GSK-J4 i neuroblastomcellinjer
Keywords: CANCER; CANCER; PHARMACOLOGY; FARMAKOLOGI; Neuroblastoma; Neuroblastom; Pediatrics; Pediatrik; Pharmacology; Farmakologi; Pharmacology and Toxicology; Farmakologi och toxikologi; Cancer and Oncology; Cancer och onkologi; Pediatrics; Pediatrik